Juridical Analysis of the Implementation of Cyber Notary in Indonesia is Associated with the Obligations of Parties to Sign Deeds Electronically - Listiyani, Novita (Jurnal Konstatering, 2022)
Article 15 paragraph (3) UUJNP notary has the authority to certify transactions conducted electronically (Cyber Notary). From the Elucidation of Article 15 paragraph (3) of the UUJNP, there is no further understanding regarding the certifying authority possessed by a notary, there is no explanation regarding the meaning of the word certifying, causing a blurring of legal norms. This article aims toknow and analyzethe implementation of Cyber Notary in Indonesia is associated with the obligations of the parties to sign the deed electronically and how legal certainty is regarding a deed made with the Cyber Notary mechanism. This research uses the sociological juridical approach method, the specification of the analytical descriptive research is how to describe the condition of the object under study, the data collection method is done by interviews and literature studies, as well as the qualitative analytical method as a method in analyzing data. Based on research results and discussion: 1)Cyber notary has begun to be implemented in Indonesia, for example inmaking of a minutes of meeting at the General Meeting of Shareholders (GMS) of a Limited Liability Company by a Notary, but using electronic media is contrary to Article 16 paragraph (1) letter m of Act No. 2 of 2014 concerning amendments to Act No. 30 of 2014 2004 concerning Notary Office; 2)With the cyber notary concept in making Authentic Deeds it is still contrary to the terms and mechanisms in the Authentic Deed itself both regulated in the Criminal Code, UUJN and UU ITE. Where there is an element of "confronting" as a formal requirement that must be fulfilled by the Notary and the parties in making an Authentic Deed, so that if these conditions are not fulfilled, the status of the deed which was originally considered an Authentic Deed which has the strongest evidentiary power can change to a deed under the hand.Keywords: Agreement; Evidence; Obligation.